Flow modeling in a porous cylinder with regressing walls using semi analytical approach - M Azimi; A Hedesh; S Karimian (International Journal of Multiphysics, 2016)
In this paper, the mathematical modeling of the flow in a porous cylinder with a focus on applications to solid rocket motors is presented. As usual, the cylindrical propellant grain of a solid rocket motor is modeled as a long tube with one end closed at the headwall, while the other remains open. The cylindrical wall is assumed to be permeable so as to simulate the propellant burning and normal gas injection. At first, the problem description and formulation are considered. The Navier-Stokes equations for the viscous flow in a porous cylinder with regressing walls are reduced to a nonlinear ODE by using a similarity transformation in time and space. Application of Differential Transformation Method (DTM) as an approximate analytical method has been successfully applied. Finally the results have been presented for various cases.